A study of the changes in how medically related events are reported in Japanese newspapers - Yukiko Kishi; Naoko Murashige; Yuko Kodama; et al (Dove Medical Press, 2010)
Yukiko Kishi1, Naoko Murashige2, Yuko Kodama1, Tamae Hamaki1, Kazuhiro Murata3, Haruka Nakada1, Tsunehiko Komatsu3, Hiroto Narimatsu1,4, Masahiro Kami1, Tomoko Matsumura11Division of Social Communication System for Advanced Clinical Research, the Institute of Medical Science, the University of Tokyo, Tokyo, Japan; 2Ministry of Health, Labor and Welfare, Aide of the Minister, Health Sector Reform Office, Tokyo, Japan; 3Department of Hematology, Teikyo University Chiba Medical Center, Chiba, Japan, 4Advanced Molecular Epidemiology Research Institute, Faculty of Medicine, Yamagata University, Yamagata, JapanAbstract: Media reports of medically related events have a major effect on the healthcare community but there have been few detailed investigations conducted to investigate their content. The Nikkei Telecom 21 database was used to investigate the number of reports concerning medically related events between 1992 and 2007 in Japan’s 5 national newspapers. For this period, both the total number of articles and the number of articles containing medically-related keywords were determined. The number of reports relating to medically related occurrences increased sharply from 1999 to 2000 and displayed a decrease from 2003 before increasing again in 2008. As of 2008, such reports account for 0.17% of total newspaper articles. The use of the word ‘iryokago’ (medical professional negligence or error) drastically increased in 1999 but showed a consistent decrease from 2004. On the other hand the frequency of reports relating to ‘litigation’ and ‘punishment’ increased rapidly in 1999 before leveling off. Despite this, the number of articles relating to medically related occurrences that were caused by doctor shortages and system errors increased sharply between 2006 and the present. Results indicate that the manner in which newspapers report medically related events is undergoing major changes.Keywords: coverage, incident, doctor shortage, system error, litigation